2005
DOI: 10.1007/s11373-005-9031-0
|View full text |Cite
|
Sign up to set email alerts
|

Taxifolin ameliorates cerebral ischemia-reperfusion injury in rats through its anti-oxidative effect and modulation of NF-kappa B activation

Abstract: SummaryInfarction in adult rat brain was induced by middle cerebral arterial occlusion (MCAO) followed by reperfusion to examine whether taxifolin could reduce cerebral ischemic reperfusion (CI/R) injury. Taxifolin administration (0.1 and 1.0 lg/kg, i.v.) 60 min after MCAO ameliorated infarction (by 42%±7% and 62%±6%, respectively), which was accompanied by a dramatic reduction in malondialdehyde and nitrotyrosine adduct formation, two markers for oxidative tissue damage. Overproduction of reactive oxygen spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(124 citation statements)
references
References 43 publications
4
115
2
Order By: Relevance
“…In contrast to this report, taxifolin has been shown to do not prevent H 2 O 2 -induced cell death in PC12 cells [19]. Taxifolin inhibits cerebral ischaemia-reperfusion injury in rats through suppression of leukocyte infiltration and by inhibition of cyclooxygenase-2 and the expression of inducible nitric oxide synthase [20]. Taxifolin glycoside reduces the microbial component-or IL-1b-induced production of cytokines and formation of reactive oxygen species and nitric oxide in dendritic cells of bone marrow and spleen [21].…”
Section: Introductioncontrasting
confidence: 84%
“…In contrast to this report, taxifolin has been shown to do not prevent H 2 O 2 -induced cell death in PC12 cells [19]. Taxifolin inhibits cerebral ischaemia-reperfusion injury in rats through suppression of leukocyte infiltration and by inhibition of cyclooxygenase-2 and the expression of inducible nitric oxide synthase [20]. Taxifolin glycoside reduces the microbial component-or IL-1b-induced production of cytokines and formation of reactive oxygen species and nitric oxide in dendritic cells of bone marrow and spleen [21].…”
Section: Introductioncontrasting
confidence: 84%
“…The induction of NFATc1 upregulates the osteoclast-specific genes expression, such as TRAP, MMP-9, and CTK. Previous studies have shown, taxifolin exerted its biological effect via modulating NF-κB signaling [22,31]. In the present research, we observed that the taxifolin treatment inhibits the RANKL-induced NF-κB pathway activation, which was accomplished by the suppression of IκBα and NF-κB p65 phosphorylation.…”
Section: Discussionsupporting
confidence: 60%
“…Researchers have demonstrated that taxifolin decreased the production of lipid radicals in a concentration-dependent manner and reduced the peroxidase activity of the complex of cytochrome c combined with dioleoyl cardiolipin, which is critical for the onset of apoptosis. Taxifolin also ameliorated cerebral ischemiareperfusion injury by inhibiting oxidative enzymes and reducing the overproduction of ROS 27,28 . Taxifolin inhibited recombinant human aldose reductase and the accumulation of sorbitol in human erythrocyte in diabetes.…”
Section: Introductionmentioning
confidence: 99%